Mr. Monk gets on board : a novel - Conrad, Hy (Obsidian, 2014)
"Of all the things that make Adrian Monk uneasy, change ranks high on the list. So when Natalie completes her P.I. license--and technically becomes Monk's boss--it's not easy for him to accept. Nor can he accept Natalie attending a business seminar at sea without him, even if it means spending a week with her on a cruise ship. Between choppy waters and obnoxious kids, Monk finds himself in a perfect storm of anxiety. Luckily, Mariah, the cruise director, is always able to smooth things over...until the crew fishes her dead body out of the water. Even after the ship's doctor declares Mariah's death an accident, Monk isn't convinced. So when the captain hires Monk and Natalie to look into a mysterious rash of vandalism on board, Monk steers the investigation toward murder..."--